Hubungan Religiusitas dengan Quarter Life Crisis Mahasiswa Semester Akhir - Dimas Agil Permadi; Pria Nurbian; Suyanti Suyanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Ideally, final-year undergraduates are expected to demonstrate psychological maturity and a clear sense of future direction. However, the pressure of academic demands and social expectations often precipitates a